Analysis of roof bearing characteristics and coal pillar stability of cemented backfill field - Xu Bin; Li Yongliang; Lu Bin; Li Jin (矿业科学学报, 2022)
In order to study the bearing characteristics of the roof and the coal pillar stability of continuous mining and continuous filling cemented filling field, a numerical analysis model based on FLAC3D is established to analyse the alternate bearing characteristics of the roof, study the conversion law of the primary and secondary bearing structures of the roof, and reveal the stress release and deformation law of the coal pillar. Based on the difference of the constraint conditions on both sides of the coal pillar, a mechanical model of the stress distribution of the coal pillar is established, and the influence law of the stress concentration coefficient, temporary support strength, burial depth and other factors on the ultimate bearing width of the coal pillar is obtained.By establishing the numerical analysis and simulation of the synergistic bearing of coal pillar and filler, the influence of the width of filler on the bearing characteristics of coal pillar is revealed. The study shows that: the bearing structure of the mine roof changes with the advancement of the working face, and the coal pillar is the main bearing structure during the co-bearing stage of the coal pillar and the filling body, and the filling body gradually transitions to the main bearing structure as the coal pillar is gradually extracted; the width of the stress equilibrium zone of the coal pillar is inversely proportional to the strength of the temporary support, and is positively proportional to the burial depth of the working face and the stress concentration coefficient, increasing the strength of the temporary support can significantly reduce the fragmentation zone of the critical surface. The increase in the width of the filling body can effectively control the stability of the coal pillar, and its main function is to reduce the force on the coal pillar while playing a role in restraining the lateral deformation of the coal pillar. In Haoyuan coal mine, by increasing the strength and filling rate of the filling body and enhancing the restraining effect of the filling body on the coal pillar, the stability of the coal pillar is effectively guaranteed, which provides a reference for the control of coal pillar deformation under similar conditions.